An Internal Current Controlled BLDC Motor Drive Supplied with PV Fed High Voltage Gain DC-DC Converter - G. G. Raja Sekhar; Basavaraja Banakara (International Journal of Electrical and Computer Engineering (IJECE), 2018)
The paper presents an efficient speed control of brushless DC (BLDC) motor drive for photo-voltaic (PV) system fed system. A high-gain DC-DC converter is employed in the system to boost the PV system low output voltage to a level required for the drive system. High-gain DC-DC converter is operated in closed-loop mode to attain accurate and steady output. The converter (VSI) for BLDC is switched at fundamental frequency and thus reducing high frequency switching losses. Internal current control method is developed and employed for the speed control of PV fed BLDC motor. The appropriateness of the internal current controller for the speed control of PV fed BLDC motor is verified for increamental speed with fixed torque and decreamental speed with fixed torque operating conditions. The system is developed and results are developed using MATLAB/SIMULINK software